Makna Simbolik Tradisi Ménréq Bola Baru Masyarakat Bugis di Desa Tinco Berdasarkan Teori Semiotika Charles Sanders Pierce - Firdayani Firdayani; Syamsuddha Syamsudduha; Hajrah Hajrah (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. The purpose of this research is to describe the symbolic meaning of the Ménréq Bola Baru tradition of the Bugis community in Tinco village, Citta sub-district, Soppeng district using Pierce's Semiotics theory. In Pierce's Semiotics theory there are representamen, interpretants and objects. The data in this study are oral data obtained from interviews, observation, and documentation techniques. The results showed that objects and foods contained in the Ménréq Bola Baru tradition are representatives of symbolic meanings in the Ménréq Bola Baru tradition (1) mappasili, (2) mapputara mattulili bola bekka pitu, (3) mabbeqda bola, (4) mappénréq tau. Interpretation (1) mappasili, (2) mapputara mattulili bola bekka pitu (3) mabbeqda bola 4) mappénréq tau, (5) when burning incense there are embers, (6) when sprinkling incense on incense that has smoke and fire (7) coconut, (8) banana bunches, (9) jackfruit bunches, (10) pabberesseng and rice, (11) water, (12) tampi, (13) pumpkin, (14) layer cake, (15) apang, (16) ondé-ondé, and (17) indo béppa. Objects (1) bunched coconut, (2) bunched banana, (3) bunched jackfruit, (4) pabberesseng, (5) water, (6) winnow, (7) pumpkin, (8) layer cake, (9) apang, (10) ondé-ondé, and (11) indo béppa.Keywords: Meaning, Symbolic, Ménréq bola baru